Progressive multifaceted approach to the management of geriatric patients with cardiac arrhythmias - A. N. Ilnitski; K. I. Prashchayeu; E. I. Korshun; E. S. Kravchenko; M. A. Pokachalova (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To develop a progressive multifaceted approach to the management of geriatric patients with cardiac arrhythmias.Material and methods. The study was carried out in 2 stages. The study sample consisted of 262 elderly and senile people (mean age, 69,5±1,1 years). There 145 elderly (mean age, 68,4±1,2 years) and 117 senile patients (mean age 74,4±1,3 years). We analyzed medications used for six months in geriatric patients with arrhytmias and senile asthenia (SA) and without it. The combined strategy of management of geriatric patients with arrhytmias and SA was tested.Results. SA is most common in geriatric patients who are taking drugs such as class I a, b, c antiarrhythmics, class V antiarrhythmics (cardiac glycosides), diuretics (torasemide, furosemide), and statins. This indicates the need to avoid polypharmacy and to adjust the treatment of geriatric patients with cardiac arrhythmias in accordance with Beers criteria. Presented study revealed that in patients with SA, the total antioxidant activity is reduced, which indicates the need to restore antioxidant defence to such patients. A combined strategy has been developed for the management of geriatric patients with cardiac arrhytmias and SA.Conclusion. The combined strategy of managing older patients with arrhytmias and SA helped to improve the geriatric status, prevent SA, and increase antioxidant defence. A significant improvement in the quality of life was noted, in particular, in relation to the mental and psychological well-being.